Caracterização Hídrica Espacial e Sazonal de Mato Grosso do Sul com Dados em Grid - Aparecido, Lucas Eduardo De Oliveira; Moraes, José Reinaldo Da Silva Cabral De; Meneses, Kamila Cunha De [UNESP]; Torsoni, Guilherme Botega; Costa, Cicero Teixeira Silva (Sociedade Brasileira de Meteorologia, 2020)
The use of global atmospheric reanalysis data (ERA-Interim) produced by the European Center for Medium Range Weather Forecasts (ECMWF) becomes an important tool for agricultural production regions, especially in scarce weather station areas. We sought to characterize the spatial and seasonal water variability of the state of Mato Grosso do Sul using meteorological reanalysis data from ERA-Interim. The study was conducted in Mato Grosso do Sul, located in the Midwest region of Brazil. Decendial rainfall and mean air temperature data were obtained from ERA-Interim between 1989 and 2015, totaling 566 points. We estimated soil water storage, water deficit and water surplus from the normal water balance of Thornthwaite and Mather (1955). In Mato Grosso do Sul there was spatial and seasonal variation of water balance components. Seasonal variation in soil water storage occurred with the change of seasons. The southern region of the state of Mato Grosso do Sul has the largest water resources, with reduced DEF, close to 100% ARM and high EXC. The largest water surpluses occur from December to March, while from August to October the lowest water surpluses occur in the state.

A utilização dos dados de reanálise atmosférico global (ERA-Interim), produzidos pelo European Centre for Medium Range Weather Forecasts - ECMWF se torna uma importante ferramenta para regiões de produção agrícola, principalmente em áreas escassas de estações meteorológicas. Objetivou-se neste trabalho, caracterizar a variabilidade espacial e sazonal hídrica do estado do Mato Grosso do Sul usando dados de reanálise meteorológica do ERA-Interim. O estudo foi realizado no Mato Grosso do Sul, localizado na região Centro-Oeste do Brasil. Os dados decendiais de precipitação pluvial e temperatura média do ar foram obtidos pelo ERA-Interim entre os anos de 1989 e 2015, totalizando 566 pontos. Estimou-se o armazenamento de água no solo, a deficiência hídrica e o excedente hídrico a partir do balanço hídrico normal de Thornthwaite e Mather (1955). No Mato Grosso do Sul ocorreu variação espacial e sazonal dos componentes do balanço hídrico. A variação sazonal do armazenamento hídrico do solo ocorreu com a mudança das estações do ano. A região sul do estado do Mato Grosso do Sul apresenta os maiores recursos hídricos, com DEF reduzido, ARM próximo de 100% e EXC elevados. Os maiores excedentes hídricos ocorrem no período de dezembro a março, enquanto, de agosto a outubro ocorrem os menores valores de excedentes hídricos no estado.
Spatial and Seasonal Water Characterization of Mato Grosso do Sul with Grid Data
Keywords: water balance components; variability; ECMWF; grid data; componentes do balanço hídrico; variabilidade; ECMWF; dados em grid